Importance of the pig as a human biomedical model - Lunney, Joan K; Van Goor, Angelica; Walker, Kristen E; Hailstock, Taylor; Franklin, Jasmine; Dai, Chaohui (Science translational medicine, 2021)
Pigs have substantial potential as biomedical models for studying human developmental processes, congenital diseases, and pathogen response mechanisms in addition to utility as xenotransplant organ donors and tools for vaccine and drug design. The similarity of pigs to humans in anatomical size and structure, physiology, immunology, and genome enhances their potential as models for humans. Hence, it is imperative that research is relevant and reproducible in animal models that more closely resemble humans, such as the pig. This review summarizes the current status of pigs as an investigative model for humans and highlights their future applications.